Left to die: the fate of the Catalan consumer cooperative movement during the primer franquismo (1939–59). Issue 4 (4th July 2022) - Garner, Jason
ABSTRACT: During the 1930s, the Catalan cooperative movement finally became a movement of the masses, but Franco's victory in the Civil War put an end to its expansion and to almost the whole movement. This article charts the consumer cooperatives' fortunes in the Barcelona Province during the first 20 years of the new regime. It covers Francoist policies towards consumer cooperatives and the obstacles these and the bleak economic situation presented, focusing on the work of the organization created by the new National Syndicalist state apparatus: the Barcelona Territorial Union of Consumer Cooperatives (UTECO).